A heat flux modulator from carbon nanotubes. Issue 32 (29th July 2015) - Jiang, Shaohui; Zhang, Guang; Xia, Dan; Liu, Changhong; Fan, Shoushan
Abstract : A suspended carbon nanotube sheet achieved heat flux modulation along its length through an pendent block. Abstract : For a heat flux modulator, the most difficult problem is that the main carriers named 'phonons' have little response to external fields. Of the existing studies on heat flux modulators, most were theoretical work and the materials systems for the theoretical calculations were artificial lattices. In this paper, we made a heat modulator with ultrathin buckypaper which was made of multi-layer carbon nanotube sheets overlapped together, and achieved an on/off ratio whose value was 1.41 using an pendent block in experiments without special optimizations. When the temperatures of the two sides were of appropriate values, we could even see a negative heat flux. Intuitively, the heat flux was tuned by the gap between the buckypaper and the pendent gate, and we observed that there was heat transferred to the pendent block. The structure of the modulator is similar to a CNT transistor with a contactless gate, hence this type of micromodulator will be easy to manufacture in the future.